2021
DOI: 10.1007/s12031-021-01919-2
|View full text |Cite
|
Sign up to set email alerts
|

Revelation of Pivotal Genes Pertinent to Alzheimer’s Pathogenesis: A Methodical Evaluation of 32 GEO Datasets

Abstract: Alzheimer’s disease (AD), a dreadful neurodegenerative disorder that affects cognitive and behavioral function in geriatric populations, is characterized by the presence of amyloid deposits and neurofibrillary tangles in brain regions. The International D World Alzheimer Report 2018 noted a global prevalence of 50 million AD cases and forecasted a threefold rise to 139 million by 2050. Although there exist numerous genetic association studies pertinent to AD in different eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…This observation reflects that when neurons are subjected to high stress, the nearby astrocytes become reactivated and migrate towards these neurons to support their survival (55). Meanwhile, consistent with previous transcriptional studies in AD (5659), ENC1 , CALM2 , CCK, RGS4 were downregulated in the pseudo-spots covering highly stressed Ex ( Fig. 3G ).…”
Section: Resultssupporting
confidence: 92%
“…This observation reflects that when neurons are subjected to high stress, the nearby astrocytes become reactivated and migrate towards these neurons to support their survival (55). Meanwhile, consistent with previous transcriptional studies in AD (5659), ENC1 , CALM2 , CCK, RGS4 were downregulated in the pseudo-spots covering highly stressed Ex ( Fig. 3G ).…”
Section: Resultssupporting
confidence: 92%
“…A study by Zhang et al also showed that ENC1 played an important role in the mitogen-activated protein kinase ( MEK )/extracellular signal-regulated kinase ( ERK ) pathway to promote cervical cancer ( 18 ). Evidence has shown that ENC1 also was one of the key genes involved in the pathogenesis of Alzheimer's disease ( 19 ). He et al found that upregulated ENC1 predicts unfavorable prognosis and correlates with immune infiltration in endometrial cancer ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several of these 29 genes have been previously reported to be associated with Alzheimer's Disease: overexpression of ANGPT1* has been found to increase amyloid beta secretion (Peng et al, 2020) whilst CLEC4G suppresses amyloid beta (Kizuka et al, 2015), and increased levels of ENC1 (Gns et al, 2022;White et al, 2017) and NPTX2 (Belbin et al, 2020;Libiger et al, 2021;Shao et al, 2020;Xiao et al, 2017) Note: Pearson's r values for the correlation between brain-g associations and brain-gene expression component profiles. Note that these are for linear associations using the absolute gene-expression component scores.…”
Section: Associations Between G and Individual Genesmentioning
confidence: 99%